Evidence for decreased parasympathetic response to a novel peer interaction in older children with autism spectrum disorder: a case-control study - Muscatello, Rachael A. (J Neurodev Disord, 2021)
BACKGROUND: Individuals with autism spectrum disorder (ASD) often experience elevated stress during social interactions and may have difficulty forming and maintaining peer relationships. The autonomic nervous system (ANS) directs physiological changes in the body in response to a number of environmental stimuli, including social encounters. Evidence suggests the flexibility of the ANS response is an important driving factor in shaping social behavior. For youth with ASD, increased stress response and/or atypical ANS regulation to benign social encounters may therefore influence social behaviors, and, along with developmental and experiential factors, shape psychological outcomes. METHODS: The current study measured ANS response to a peer-based social interaction paradigm in 50 typically developing (TD) children and 50 children with ASD (ages 10–13). Respiratory sinus arrhythmia (RSA), a cardiac measure of parasympathetic influence on the heart, and pre-ejection period (PEP), a sympathetic indicator, were collected. Participants engaged in a friendly, face-to-face conversation with a novel, same-aged peer, and physiological data were collected continuously before and during the interaction. Participants also reported on state anxiety following the interaction, while parents reported on the child’s social functioning and number of social difficulties. RESULTS: Linear mixed models revealed that, while there were no diagnostic effects for RSA or PEP, older youth with ASD appeared to demonstrate a blunted parasympathetic (RSA) response. Further, increased severity of parent-reported social symptoms was associated with lower RSA. Youth with ASD reported more anxiety following the interaction; however, symptoms were not related to RSA or PEP response based on linear mixed modeling. CONCLUSIONS: Physiological regulation, age, and social functioning likely influence stress responses to peer interactions for youth with ASD. Parasympathetic functioning, as opposed to sympathetic arousal, may be especially important in behavioral regulation, as older youth with ASD demonstrated atypical regulation and response to the social interaction paradigm. Future studies should help to further elucidate the developmental factors contributing to stress responses in ASD, the impact of physiological response on observable social behavior, and potential long-term consequences of chronic social stress in youth with ASD. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s11689-020-09354-x.